Improving student housing services at Umm Al-Qura University: A proposed perception - Al-Qarni, Saad Rafea (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the reality of the services provided by Umm Al-Qura University to its students in the field of student housing, and to provide a proposed vision for the development of student housing service at Umm Al-Qura University in light of global experiences. The study used the descriptive and analytical method. The study population consisted of university housing students (scholarships students) at Umm Al-Qura University, and the sample size reached 104 students. The researcher used the questionnaire as a study tool. Among the most important findings of the study: There is great satisfaction on the part of the housing students on the housing administration’s dealings with students. The results showed the students' need to hold open dialogue meetings with the housing administration to exchange experiences, transfer expertise and experiences, and listen to different points of view through the establishment of trips and entertainment tours, there are places in the housing for the practice of various student activities. Among the most important findings of the study: Building additional housing units, taking into account when designing, increasing the size of apartments and rooms, establishing a public park around student housing to increase the percentage of oxygen and in order to become an outlet for students' free time, establish communication channels between students and the administration of student housing after the student’s graduation from the university, to benefit from the multinationality through language courses and cultural
Keywords: Improve services; Housing; Student housing; Umm Al Qura University